Contemporary global issues in human resource management - Turkmenoglu, Mehmet Ali, 1986-; Cicek, Berat, 1984- (Emerald Publishing Limited, 2020)
Globalization, digitalization and social changes are rapidly impacting the world of business and in-turn, Human Resource Management practices. The book examines issues that employees encounter in the workplace: ethics, diversity, discrimination, generational differences, conflicts, participation, digitalization and work-life balance. Practitioners and researchers will gain enhanced understanding and awareness of these issues and more as they are investigated through an interdisciplinary, international and critical point of view.